THE LIVING QUR’AN IN MARITIME CULTURE: SYMBOLISM, RITUAL, AND ECOLOGICAL SPIRITUALITY IN THE TASELA BOATMAKING TRADITION - Muhamad Khabib Imdad; Tami Dewi Puspa Rahayu; Suciyadi Ramdhani; Busro (Penamas, 2025)
This study explores the Nurunkeun Jampanan ritual and the Tasela boatmaking tradition in Cikawung-Ading Village, Tasikmalaya, as a manifestation of the living qur’an within Indonesia’s maritime culture. It examines how Qur’anic teachings are embodied in local rituals and collective practices that sustain the spiritual and ecological harmony of coastal communities. Using a qualitative ethnographic method through interviews, participatory observation, and documentation, the research reveals three main dimensions: (1) the recitation of Surah al-Fātiḥah and al-Ikhlāṣ as expressions of tauhīd and communal devotion; (2) the annual limitation of five boats symbolizing the Qur’anic concept of mīzān (balance) and moderation; and (3) the ritual’s social function in reinforcing solidarity and environmental awareness. These findings demonstrate that Qur’anic values are actualized through living cultural expressions integrating spirituality, social ethics, and ecological responsibility. The study contributes to Qur’anic anthropology and Islamic ecology by showing how sacred texts are lived and interpreted in maritime settings. Practically, it proposes recognizing Nurunkeun Jampanan as an intangible cultural heritage with religious-ecological significance and promoting Qur’anic ecological ethics in coastal education, thus bridging Qur’anic studies, anthropology, and environmental ethics within Indonesia’s coastal Islam.